Perlindungan Hukum Bagi Perempuan Yang Melakukan Pengguguran Kandungan (Aborsi) - Sevia, Melina Dwi; Nofitasari, Solehati; Wahyuningtyas, Yuli Winiari; Manab, Abdul (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
The crime of rape is a sexual crime that can be committed by force between the perpetrator and the victim which can cause the victim to suffer physical, mental, and psychological disorders. The type of rape crime tends to be sexual so that it is familiar in society as it is carried out following developments in the era in Indonesia where cases of rape are increasing over time. Abortion itself is regulated in Law Number 17 of 2023 concerning Health that abortion is permitted with the provisions that have been regulated. Abortion is a controversial issue, and strict supervision and clear regulations are needed. Legal protection is very important to provide human rights, especially reproductive health services. Efforts to protect the newspaper are regulated in Government Regulation Number 35 of 2020 concerning compensation, restitution and assistance to Witnesses and Victims, providing a form of protection for rape victims can be realized in the form of restitution and compensation, medical services and legal assistance. This law also ensures that victims have fair and fast access to abortion services, while preventing possible misuse of these provisions.